(Ig)Easy diagnosis of disseminated coccidioidomycosis. Issue 3 (8th March 2022) - Azeem, Ahad; Quimby, David; Krajicek, Bryan; Horne, John
Abstract : An immunocompetent man in his 20s came to the hospital for shortness of breath, fevers and lower back pain with unintentional 20 lbs. weight loss. Relevant history included a recent trip to Arizona 3 months prior to presentation. On arrival, he was noted to have decreased breath sounds bilaterally, and paraspinal tenderness in the lumbar area. CT scan revealed diffuse pneumonitis and an abscess with osteomyelitis in the sacrum and right iliac bone. Continued respiratory decompensation led him to the intensive care unit where he had a bronchoscopy and later sacroiliac joint fluid collection was performed. Based on his travel history, and elevated serum IgE, liposomal amphotericin B was initiated. Later his antibodies against Coccidiodes resulted elevated and fungal cultures from the bronchoalveolar lavage and abscess from the sacral vertebrae grew mould, morphologically consistent with Coccidiodes posadasii . He was transitioned to oral fluconazole and will have a close follow-up outpatient.